Gender Parity Progress: Assessing Women's Representation in Nepal's Second Constituent Assembly Elections (CAE) (Samsad Journal संसद जर्नल, 2024)
This research provides a comprehensive examination of the status of women in Nepal, focusing particularly on their participation in the second Constituent Assembly Elections (CAE). It offers insights into the need for future policy and decision-making processes to prioritize women's empowerment through the electoral system, ensuring their meaningful political representation in line with democratic principles. The study analyzes media coverage of women in politics from September to December 2013, during the period of the second CAE. Through qualitative explanatory analysis, it argues that the failure of the first CAE to draft a new constitution for Nepal led to the necessity of a second election within a short span of five years. Inclusion, especially of women, was a prominent theme in both elections. While the first CAE was praised for its inclusivity, particularly in terms of women's representation, the second CAE fell short in this regard. The research concludes that the second Constituent Assembly Election (CAE) witnessed not only a reduced number of female candidates but also a lower success rate among them. It explores the reasons behind this disparity, the issues raised by women candidates, their demands, and offers a comprehensive conclusion on the overall issue.